In vivo color changes of esthetic orthodontic ligatures - Andréia Viana Martins da Silva; Giselle Vasconcelos de Mattos; Carlos Mario Kato; David Normando (Dental Press Journal of Orthodontics, 2012)
OBJECTIVE: To assess the color changes that occur in four commercial brands of esthetic orthodontic elastomeric ligatures after exposure to the oral environment. METHODS: The four elastomeric ligatures manufacturers mostly mentioned by orthodontists were investigated: Morelli, Uniden, American Orthodontics (AO) and TP. The sample comprised 25 patients. The elastomeric ligatures were randomly distributed and arranged in the four dental quadrants of each patient, r for 30 days. After this period, two units of each brand were photographed in a standardized manner. Subsequently, color changes were visually evaluated and assigned a score (0, 1, 2 or 3) by a panel of four examiners. The mean scores assigned by the examiners were statistically analyzed by ANOVA and Tukey's test (p < 0.05). RESULTS: The mean pigmentation scores assigned to Morelli (1.80 ± 0.78) and Uniden (1.92 ± 0.66) elastomeric ligatures after 30 days in the oral environment were not statistically different. However, these brands were significantly more pigmented after 30 days in the oral environment (p < 0.01) compared to American Orthodontics (0.97 ± 0.6) and TP (0.83 ± 0.79). CONCLUSIONS: Although all four brands exhibited an undesirable pigmentation after 30 days in the oral environment, color change for American Orthodontics and TP Orthodontics ligatures was significantly lower than Morelli and Uniden products. OBJETIVO: avaliar as alterações de cor ocorridas em elastômeros estéticos de quatro marcas comerciais, quando expostos ao meio bucal. MÉTODOS: foram examinadas as quatro marcas comerciais mais citadas por ortodontistas - Morelli, Uniden, American Orthodontics (AO) e TP -, em 25 pacientes consecutivos. Os elastômeros foram distribuídos de forma aleatória e ordenados nas quatro hemiarcadas de cada paciente, permanecendo no meio bucal por 30 dias. Após esse período, duas unidades de cada marca em todos os pacientes foram fotografadas de forma padronizada para, posteriormente, serem analisadas através de avaliação visual quanto à variação de cor, por escores (0, 1, 2, 3), por um painel de quatro examinadores. Os escores médios dos examinadores foram analisados estatisticamente por meio da ANOVA e teste de Tukey, com p<0,05. RESULTADOS: os escores médios de pigmentação, após 30 dias no meio intrabucal, obtidos para os elastômeros Morelli (1,80±0,78) e Uniden (1,92±0,66) não foram estatisticamente diferentes entre si. Entretanto, essas marcas estavam significativamente mais pigmentadas após 30 dias no meio intrabucal (p<0,01) quando comparadas às marcas importadas, American Orthodontics (0,97±0,6) e TP (0,83±0,79). CONCLUSÃO: apesar de todas as quatro marcas apresentarem uma indesejável pigmentação após 30 dias no meio intrabucal, as marcas American Orthodontics e TP apresentaram alterações de cor menos significativas do que as marcas Morelli e Uniden.